2002
DOI: 10.1046/j.1528-1157.2002.21601.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Statistical Parametric Mapping and SPECT Difference Imaging in Patients with Temporal Lobe Epilepsy

Abstract: Summary:Purpose: Statistical parametric mapping (SPM) is an image-analysis tool that assesses the statistical significance of cerebral blood flow (CBF) changes on a voxel-by-voxel basis, thereby removing the subjectivity inherent in conventional region-of-interest (ROI) analysis. Our platform of single-photon emission computed tomography (SPECT) ictalinterictal difference imaging in clinical epilepsy has been validated for localizing seizure onset. We extend the tools of SPM by further applying statistical mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(80 citation statements)
references
References 16 publications
3
76
0
1
Order By: Relevance
“…For example, neuroimaging studies in humans have shown decreased cerebral blood flow (CBF) in frontal and parietal cortex during these events [18,51,59] as well as with interictal discharges [39] causing deactivation in bilateral posterior cingulate during interictal spikes [37].…”
Section: Default Mode Network Involvement In Complex Partial Seizuresmentioning
confidence: 99%
“…For example, neuroimaging studies in humans have shown decreased cerebral blood flow (CBF) in frontal and parietal cortex during these events [18,51,59] as well as with interictal discharges [39] causing deactivation in bilateral posterior cingulate during interictal spikes [37].…”
Section: Default Mode Network Involvement In Complex Partial Seizuresmentioning
confidence: 99%
“…In addition to visual inspection, BSI is also suitable for statistical analysis. Statistical analysis of BSI has been used to analyze the regions of the brain that show diff e rences in perfusion in pathologies such as Alzheimer's disease 4 , systemic lupus erythematosus 5 and in the evaluation of epileptic foci in BSI [6][7][8] .…”
Section: Resumo -Objetivo: Investigar O Padrão De Anormalidades Perfumentioning
confidence: 99%
“…9 A similar approach subsequently was developed and evaluated by others using control data from pairs of SPECT scans of each of 7 nonneurologic patients, but their method was not compared with other more established methods such as SISCOM. 10 The aim of this study was to objectively compare our new method of SPM analysis of ictal-interictal difference data (statistical ictal SPECT coregistered to MRI [STATISCOM]) with SISCOM by using the same raw SPECT data from each patient.…”
Section: Discussionmentioning
confidence: 99%